A COUPLED MODEL SIMULATION OF THERMAL DISPERSION USING CELLULAR AUTOMATA AND NUMERICAL HYDRODYNAMIC MODEL - Amri, Faisal
In this research a coupled model was used to simulate a thermal dispersion phenomenon that caused by a continuous source that came out from an outlet in a 10 km x 1 km-sized tidal channel. The thermal dispersion was simulated by using cellular automata while the hydrodynamic condition in the channel was simulated by numerical model. The hydrodynamic condition in the channel was simulated in these schemes : tidal force in the opened boundary, constant outflow rate from the outlet which was 0,4 m/s, and several wind conditions (westerlies and easterlies) as the current generator. The cellular automata model used Von Neumann neighborhood in the advection procces with the cell (main and neighbooring) weighting coefficent (kSUA and kSTA) defined as